Orthostatic Hypotension and Risk of Clinical and Subclinical Cardiovascular Disease in Middle‐Aged Adults - Stephen P. Juraschek (Wiley, 2018)
BackgroundAlthough orthostatic hypotension (OH) is a well‐recognized manifestation of neuropathy and hypovolemia, its contribution to cardiovascular disease (CVD) risk is controversial. Methods and ResultsParticipants with OH, defined as a decrease in blood pressure (systolic ≥20 mm Hg or diastolic ≥10 mm Hg) from the supine to standing position, were identified during the first visit of the ARIC (Atherosclerosis Risk in Communities) Study (1987–1989) within 2 minutes of standing. All participants were followed up for the development of myocardial infarction, heart failure, stroke, fatal coronary heart disease (CHD), any CHD (combination of silent, nonfatal, and fatal CHD or cardiac procedures), and all‐cause mortality. Participants were assessed for carotid intimal thickness and plaque during the first visit. Detectable high‐sensitivity troponin T (≥5 ng/L) and elevated NT‐proBNP (N‐terminal pro‐B‐type natriuretic peptide; ≥100 pg/mL) were determined in blood collected during the second visit (1990–1992). All associations were adjusted for known CVD risk factors. In 9139 participants (57% women; 23% black; mean age, 54±5.7 years), 3% had OH. During follow‐up (median, 26 years), OH was associated with myocardial infarction (hazard ratio [HR], 1.88; 95% confidence interval [CI], 1.44–2.46), congestive heart failure (HR, 1.65; 95% CI, 1.34–2.04), stroke (HR, 1.83; 95% CI, 1.35–2.48), fatal CHD (HR, 2.77; 95% CI, 1.93–3.98), any CHD (HR, 2.00; 95% CI, 1.64–2.44), and all‐cause mortality (HR, 1.68; 95% CI, 1.45–1.95). OH was also associated with carotid intimal thickness (β, 0.05 mm; 95% CI, 0.04–0.07 mm), carotid plaque (odds ratio, 1.51; 95% CI, 1.18–1.93), detectable high‐sensitivity troponin T (odds ratio, 1.49; 95% CI, 1.16–1.93), and elevated NT‐proBNP (odds ratio, 1.92; 95% CI, 1.48–2.49). ConclusionsOH identified in community‐dwelling middle‐aged adults was associated with future CVD events and subclinical CVD. Further research is necessary to establish a causal role for OH in the pathogenesis of CVD.